Bimbingan Teknis Pertanian Organik sebagai Penerapan Teknologi Budidaya Ramah Lingkungan kepada Perkumpulan Kelompok Tani Gapsera Sejahtera Mandiri - Dulbari Dulbari; Yuriansyah Yuriansyah; Hery Sutrisno; Arief Maksum; Destieka Ahyuni; Lina Budiarti; Hidayat Saputra; Miranda Ferwita Sari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Organic agriculture was a cultivation system that applies the concept of sustainable agriculture. Organic farming systems depend on natural ingredients without using synthetic chemicals. Organic cultivation was environmentally friendly by farming activities by continuing to minimize negative impacts on the surrounding environment. This activity aims to provide knowledge and skills on the concept of sustainable agriculture, which is carried out through the application of an organic farming system at Polinela Organic Farm. Technical guidance activities are carried out at the Polinela Organic Farm, Lampung State Polytechnic, on Tuesday, March 10, 2020. Participants were the Association of ‘Sejahtera Mandiri’ Farmers Groups Rejo Asri Village, Seputuh Raman, Central Lampung. The application of environmental friendly in agricultural aspects was reflected in the management of the concept of organic agriculture carried out by Polinela Organic Farm. The concept of environmental friendly in agricultural development was implemented by taking into various aspects, such as the use of inorganic fertilizers with high efficiency, the application of pest and disease control by notice the natural ecological balance, the application of integrated crop management, the application of a clean and healthy farming system, the maintenance and strengthening of physical fertility, chemical, and biological in nature and the use of effective technology based on local wisdom.